A critical approach to existing management perspectives in Scuba Diving: A step in defining ecological carrying capacity - Hipólito, Cláudia (2024)
There are a considerable number of studies reporting the negative impacts of recreational diving and their causes, yet there is a gap in the information regarding the aspects of activity management. This paper presents a systematic approach to the management measures found in the literature. A large part of the measures identified address stakeholders’ awareness, data on the activity, and implementing adapted management measures. Stakeholders need to be integrated into the entire process of managing the activity because they are the target for correcting actions. A knowledge gap of the evaluation of the “ecological carrying capacity” of dive sites exists, along with a lack of methods for its assessment. This study informs future steps on the development of an integrated management and monitoring model that encompasses the assessment of ecological carrying capacity in further research. It also brings a vision of sustainable management of the recreational diving activity by advancing the conceptual framework of scuba diving and tourism integrated management.